Mark and Paul : Comparing the oldest extant literary works and theological ideas of early Christianity - Mader, Heidrun E. (Biblische Zeitschrift - Supplements, 2024)
What is the relationship between the earliest Gospel-Mark-and the first congregational letters of the apostle Paul? Heidrun E. Mader provides a comprehensive overview of the relationship between the Pauline epistles and the Gospel of Mark. She addresses several themes that Paul and Mark treat in similar ways and integrates them into a consistent overall picture. The following themes are addressed: the universalistic concept of the gospel; the integration of gentiles in Christ; the place of the Torah in early Christian community life; the central role of the cross. Mader shows that there are specific and exclusive similarities between Paul and Mark that go beyond commonalities with other ancient writings. However, the results do not necessarily suggest direct literary dependence. Pauline theology could also have been transmitted orally, especially if we accept the hypothesis that Mark lived in Rome, where he could have encountered Paul himself in the early 60s.